GESTION DE LA BIODIVERSITE : RELATIONS AUX PLANTES ET DYNAMIQUES VEGETALES CHEZ LES DANI DE LA VALLEE DE LA BALIEM EN IRIAN JAYA, INDONESIE - Yohanes - Purwanto (REINWARDTIA, 2002)
PURWANTO, Y. 2002. Biodiversity management: Plant relation of the Dani people and vegetation dynamic in the Baliem valley of Irian Jaya, Indonesia. Reinwardtia 12(1): 1–94. ? The study was conducted in two approaches, ethnobotanical approach and ecological approach. Ethnobotanical approach consists of knowledge analization and plant nature environment uses which consists of spatial organization, botanical indigenous knowledge, traditional system on plant nomenclature, and treats the agriculture activities of the Dani–Baliem. Whereas, the later approach we analyse the floristic diversity in different environment existence in the Baliem Valley. In this ecological approach contains of analyse floristic of the primary forest of different altitude, secondary forest (fallow system of different ages), transition zone (zone ecotone), home garden, villages, protection area and sacred sites. The result indicated that the degradation of environment in the Baliem Valley, principally caused by agricultural activity and exploitation of natural resources. The traditional agricultural activities of Dani–Baliem society influence on decreasing of genetic resources on wild plant (wild species).On the contrary, these activities in the intraspecific diversity level,increase the number of cultivated plants. Further, Dani–Baliem people activities also influence the ecological diversity. This can be seen from different unit of environment existence like secondary forest, agricultural area, protection zone, sacred site, habitation areas etc.), where every unit have a specific use and a specific plant diversity.